A Mapping of Labor Mobility Costs in the Developing World - Erhan Artuç; Daniel Lederman; Guido Porto (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2013)
Estimates of labor mobility costs are needed to assess the responses of employment and wages to a trade shock when factor adjustment is costly. Available methods to estimate those costs rely on panel data, which are seldom available in developing countries. In this paper, we propose a method to estimate mobility costs using data that is more easily obtainable worldwide. Our estimator matches observed employment flows with those flows predicted by a model of costly labor adjustment. We estimate a mapping of labor mobility costs for the developing world and we use those estimates to explore the response of labor markets (wages and employment) to trade policy.
Keywords: F16; D58; J2; J6; 330; World Labor Mobility Costs; Wage Dynamics; Employment Dynamics